AI Chatbots as the New Authority on Muslim Household Consultations: A Gender and Islamic Law Analysis - Nerisma Eka Putri; Randu Rahmatan Hanif; Muhammad Azkia Fahmi (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2026)
AI has transformed the way Muslim households seek advice. The purpose of this study is to evaluate AI chatbots as a new authority in Muslim household counseling from the perspectives of gender and Islamic law. This study analyzes aspects of artificial intelligence, social construction, gender relations, and Islamic legal legitimacy arising from the use of AI chatbots to resolve household issues. Data was obtained through responses from AI chatbots such as OpenAI ChatGPT as well as literature related to gender, Islamic law, and digital technology. The results of the study indicate that AI chatbots form a new authority that is instant, practical, and appears neutral, yet lacks the legitimacy of ijtihad in Islamic law. From a gender perspective, AI has the potential to reproduce patriarchal biases while simultaneously generating narratives of equality that are not always aligned with the principles of Islamic law. This study affirms that AI cannot be positioned as a religious authority, but rather only as an information tool.